Strain-polarization coupling mechanism of enhanced conductivity at the grain boundaries in BiFeO3 thin films - Alikin, Denis; Fomichov, Yevhen; Reis, Saulo Portes [UNESP]; Abramov, Alexander; Chezganov, Dmitry; Shur, Vladimir; Eliseev, Eugene; Kalinin, Sergei V.; Morozovska, Anna; Araujo, Eudes B. [UNESP]; Kholkin, Andrei (Elsevier B.V., 2020)
Charge transport across the interfaces in complex oxides attracts a lot of attention because it allows creating novel functionalities useful for device applications. It has been observed that movable domain walls in epitaxial BiFeO3 films possess enhanced conductivity that can be used for reading out in ferroelectricbased memories. In this work, the relation between the polarization, strain and conductivity in sol-gel BiFeO3 films with special emphasis on grain boundaries as natural interfaces in polycrystalline ferroelectrics is investigated. The interaction between polarization and grain boundaries occuring at elevated temperatures during or after material sintering stage leads to the formation of branched network of highly conductive grain boundaries with the electrical conductivity about two orders higher than in the bulk. At room temperature, these conductive traces stabilized by the defects remain and do not change upon polarization switching. These collective states provide further insight into the physics of complex oxide ferroelectrics and may strongly affect their practical applications, because reveal an additional mechanism of the leakage current in such systems. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: bismuth ferrite; grain boundaries; conductivity; interfaces; domain structure